2015
DOI: 10.1038/onc.2015.220
|View full text |Cite
|
Sign up to set email alerts
|

ErbB3 upregulation by the HNSCC 3D microenvironment modulates cell survival and growth

Abstract: Head and neck squamous carcinomas (HNSCC) present as dense epithelioid three-dimensional (3D) tumor nests that can mediate signals via the human epidermal growth factor receptor (ErbB) tyrosine kinase family to promote intratumoral survival and growth. We examined the role of the tumor microenvironment on ErbB receptor family expression and found that the status of intercellular organization altered the receptor profile. We showed that HNSCC cells forced into tumor island-like 3D aggregates strongly upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…In addition, upon stimulation with ligands the extent of phosphorylation of EGFR and c-MET was lower in the 3D cultures [ 112 ]. Similarly, alterations in ErbB3 expression and phosphorylation were previously shown to modulate cell survival and growth in a 3D microenvironment [ 63 ].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, upon stimulation with ligands the extent of phosphorylation of EGFR and c-MET was lower in the 3D cultures [ 112 ]. Similarly, alterations in ErbB3 expression and phosphorylation were previously shown to modulate cell survival and growth in a 3D microenvironment [ 63 ].…”
Section: Discussionmentioning
confidence: 98%
“…Relative to two-dimensional monolayer cultures, ERBB3 protein expression is much higher in multicellular aggregate three-dimensional cultures of head and neck squamous carcinomas; furthermore, ERBB3 signaling pathways operate continuously in multicellular aggregate cultures despite low levels of ERBB2 and EGFR expression. 87 Responses to drugs targeting ERBB receptors also differ between two-dimensional monolayer and multicellular aggregate cultures. 88 Although relatively few such comparisons have been performed to date, it will be important to bear in mind the impact of culture methods as we continue to dissect the role that ERBB3 plays in human cancer and assess new therapeutic agents targeting this receptor tyrosine kinase.…”
Section: Erbb3 In Human Cancermentioning
confidence: 99%
“…This suggested that ErbB3 signaling is particularly important for aspects of tumor growth related to the in vivo tumor microenvironment that are not required for in vitro growth. In three-dimensional in vitro culture systems, ErbB3 has been shown to be upregulated by HIF1α 46 , which is particularly important as tumors grow beyond their blood supply and encounter a hypoxic environment. In addition, in some contexts, EGFR promotes HIF1α stabilization primarily through its ability to activate the PI3 kinase-AKT pathway (Heeg et al and references therein 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…EGFR itself has been reported to drive HIF1α expression in some systems 53 , but we did not observe any effect of Cetuximab on HIF1α levels in controlled CoCl 2 experiments. Interestingly, 3D tissue culture assays of HNSCC cells have shown that linked HIF1α upregulates ErbB3 46 . Our data suggest that regulation may occur in both directions, as suppression of ErbB3 significantly reduced the ability of CoCl 2 -induced hypoxia signaling to upregulate HIF1α.…”
Section: Discussionmentioning
confidence: 99%